1958
DOI: 10.1017/s0080456800009534
|View full text |Cite
|
Sign up to set email alerts
|

XVI.—Cytological Studies of Melaniidæ (Mollusca) with Special Reference to Parthenogenesis and Polyploidy. I. Oögenesis of the Parthenogenetic Species ofMelanoides(Prosobranchia-Gastropoda)

Abstract: SynopsisA Study of the oögenesis and maturation in four species of melaniid snails, viz. Melanoides tuberculatus—diploid race 2n = 32, M. tuberculatus—polyploid race with 90-94 chromosomes, M. lineatus—polyploid with 71-73 chromosomes and M. scabra—polyploid with 76-78 chromosomes, showed these species to be thelytokous. These are instances of ameiotic parthenogenesis with two equational maturation divisions and are recorded for the first time in molluscs, the only other known instance in the animal kingdom be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
(4 reference statements)
1
30
0
Order By: Relevance
“…The multiple banding patterns observed at each locus is consistent with polyploidy in M. tuberculata (Jacob 1959). The reproducibility of these patterns is secured by: (i) repeated PCR assays on the same individuals; (ii) the fact that many individuals of a given morph have the same genotype whatever the site and year of sampling; and (iii) the fidelity of genotype transmission across generations.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The multiple banding patterns observed at each locus is consistent with polyploidy in M. tuberculata (Jacob 1959). The reproducibility of these patterns is secured by: (i) repeated PCR assays on the same individuals; (ii) the fact that many individuals of a given morph have the same genotype whatever the site and year of sampling; and (iii) the fidelity of genotype transmission across generations.…”
Section: Discussionsupporting
confidence: 61%
“…This is an expected consequence of variable ploidy levels, as well as of the origin (auto‐ vs. allopolyploidy) and age of polyploidy. The origin of polyploidy in M. tuberculata indeed involves complex and repeated allo‐ and autopolyploidization events (Jacob 1959). Allopolyploidization through hybridization may have associated more or less homologous sets of chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophoretic studies of individuals from three populations there indicated a high level of polymorphism in each population (Livshits & Fishelson, 1983). A low percentage of males has also been recorded in other populations (Jacob, 1957). Dybdahl & Lively (1995) suggested that the many clonal populations they found in Potamopyrgus antipodarum were derived from sympatric sexual populations.…”
Section: Discussionmentioning
confidence: 99%
“…This species is arguably one of the most eurytopic freshwater organisms known; although it occurs almost ubiquitously in Africa with other common freshwater molluscs in 'normal' river and lake waters, it has an astonishing resistance to extreme water chemistries (e.g. Jacob, 1957;Samaan & Aleem, 1972;Tchernov, 1973), extremely high water temperatures (e.g. Raymond, 1852), and high suspended silt loads and flocculent substrates (e.g.…”
Section: Phenotypic Variation In Freshwater Molluscsmentioning
confidence: 99%